Copyright as Fiduciary Security: Challenges and Prospects in the Digital Era - Haspada, Deny (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
In the digital era, intellectual property rights, particularly copyright, have gained significant importance as valuable assets. This study explores the utilization of copyright as a collateral for fiduciary guarantees, highlighting both the challenges and prospects in this evolving landscape. The research examines legal frameworks, regulatory developments, and judicial precedents pertinent to the use of copyright in fiduciary arrangements. Key challenges include the valuation of intangible assets, enforcement of fiduciary rights, and technological advancements that complicate copyright protection. Conversely, the prospects of leveraging copyright as fiduciary collateral are promising, offering new avenues for financing and investment. By analyzing these dynamics, the study provides insights into the potential for a more robust and adaptive legal infrastructure that accommodates the digital economy's needs. Recommendations for policymakers, legal practitioners, and stakeholders aim to enhance the practical application and legal certainty of using copyright as a fiduciary guarantee in Indonesia. This paper contributes to the broader discourse on intellectual property and financial innovation, addressing the intersection of law, technology, and commerce.